Toxic and Hazardous (B3) Solid Waste Management at Abdul Moeloek General Hospital: An Implementation Assessment in 2022 and Recommendations - Hasiany, Sillak; Naibaho, Riadi Tomson Eventius; Lisafitri, Yuni; Putri, Intan Andriani (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2023)
Making sure that the health and environment are taken care of, solid B3 Waste produced by hospitals has to be treated according to existing regulations. As an A-class hospital in Bandar Lampung, AM General Hospital commit to conducting good practices for its solid B3 waste management. This study aims to analyze the current implementation of solid B3 waste management, the compliance of AM General Hospital’s B3 waste management Standard Operation Procedure (SOP) with current regulations, and recommend improvement strategies for solid B3 waste management in AM General Hospital. For eight consecutive days in August 2022, solid B3 waste samples were collected and analyzed. The average solid B3 waste produced by AM General Hospital was 285 kg/day for infectious waste and 6.3 kg/day for sharp waste. Inpatient installation contributed the majority of solid B3 waste there. Due to the observation sheet that was created according to the regulations, 65% of AM General Hospital’s SOP involving sorting; storage; collection; transportation; and disposal has already complied with the regulations. Several shortcomings were found such as the absence of an official solid B3 waste handling report; the absence of proper labeling in the B3 waste containers; and the use of black plastic bags. Analytical Hierarchy Process (AHP) data analysis technique was deployed, resulting in a technology application and waste minimization as improvement recommendations.